2021
DOI: 10.1088/1361-6463/ac2530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed electric field on diabetes-induced glycated enzyme, oxidative stress, and inflammatory markers in vitro and in vivo

Abstract: This study focused on the effect of pulsed electric field (PEF) on the modification of superoxide dismutase (SOD) to recover its activity (in vitro) and thereby reverse oxidative stress in diabetic mice (in vivo). The result of the in vitro assay demonstrated that PEF could modify the glycated SOD structure through a change in the electrostatic environment of the protein. This modification leads to an 83% and 31% increase in the enzymatic activity of in vitro and in vivo assays, respectively. The in vivo asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Furthermore, the cytoprotective capacity of PEF extracts was linearly related to total carotenoid content and total anthocyanin content. For Yellow Solar carrots, which had a low total carotenoid content, PEF significantly increased the carotenoid content (Leong et al, 2016a;Rezaeinezhad et al, 2022). Leong et al (2016b) also found that PEF treatment shortened the immersion time and improved the protection against H 2 O 2 oxidative stress in Vitis Vinifera.…”
Section: Phenols and Carotenoidsmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the cytoprotective capacity of PEF extracts was linearly related to total carotenoid content and total anthocyanin content. For Yellow Solar carrots, which had a low total carotenoid content, PEF significantly increased the carotenoid content (Leong et al, 2016a;Rezaeinezhad et al, 2022). Leong et al (2016b) also found that PEF treatment shortened the immersion time and improved the protection against H 2 O 2 oxidative stress in Vitis Vinifera.…”
Section: Phenols and Carotenoidsmentioning
confidence: 89%
“…found that the antioxidant capacity of PEF-treated microalgae bio extracts was significantly enhanced. PEF can increase the number of nutrients synthesized in plant-based foods, which can be utilized to customize extraction parameters for low levels of active substances and synthesize more of the nutrients required by humans(Leong et al, 2016a;Rezaeinezhad et al, 2022).…”
mentioning
confidence: 99%